Perfil Sócio Econômico Dos Estudantes Concluintes No Centro De Ensino Médio Cem Professor Florêncio Aires Em Porto Nacional - To - REIS, Luiza Araujo Dos (Universidade Federal do Tocantins, 2023)
The good academic performance of a student depends on the result of the interaction of several factors intrinsic and extrinsic to the person, and the performance presented by the student during the school learning process depends, on other factors, such as social conditions, personal relationships and psychological conditions. Thus, the objective of this work was to describe the socioeconomic profile